Rosyjska opozycja wobec świata modernizmu - Jedliński, Marek (Studia Rossica Posnaniensia, 2017)
Modernity is typically defined as a post-traditional historical period. Central to modernity is emancipation from religion and consequent secularization. In my article I analyze and interpret the ideological foundations of contemporary Russian neo-Euroasianism. This movement is led by Alexander Dugin, an important representative of Russian traditionalism and conservatism. What he postulates is to build an ideocratic orthodox-soviet state, which should include Ukraine.